Head trauma in the haemophilic child and management in a paediatric emergency department: Descriptive study - García Sánchez, P.; Molina Gutiérrez, M. Á.; Martín Sánchez, J.; Inisterra Viu, L.; García García, S.; Rivas Pollmar, M. I.; Martín Salces, M.; Álvarez Román, M. T.; Jiménez Yuste, V. (Haemophilia : the official journal of the World Federation of Hemophilia, 2018)
Introduction Haemophilia is one of the most common inherited bleeding disorders in the Emergency Department (ED). The most dangerous site of bleeding is the central nervous system. Aims To describe the characteristics of haemophiliacs arrived to our ED following a head trauma and to analyse the incidence of intracranial haemorrhage (ICH). Materials and Methods Retrospective, analytical, observational study, conducted in a Paediatric ED. We included haemophilic patients aged from birth to 16 years who consulted after a head trauma over a 6‐year period. Data collected included age, type of haemophilia and head trauma, symptoms, prophylaxis status, CT imaging, treatment and number of visits to the ED. Results About 46 males and 85 episodes were analysed. The median age was 2.38 years. Severe haemophilia A was the most frequent type of disease (50%). All head injuries were mild, and the most frequent mechanism was a collision with an object (38.8%). In 62 episodes (72.9%) the patients were asymptomatic. The rest 23 events had symptomatology, being the most common headache (26%), emesis (21.7%) and drowsiness (17.4%). Head CT was obtained in 31 episodes, founding altered results in 10 (6 of them corresponding to ICH). All the patients with ICH had symptomatology. About 37 episodes required admission. Conclusion Intracranial haemorrhage is one of the most dangerous events in haemophiliacs and it may occur after a head trauma. Our study suggests that, in case of head trauma, CT must be obtained in symptomatic patients and in those with additional risk factors. Asymptomatic patients must have prolonged observation.